A link between LRRK2, autophagy and NAADP-mediated endolysosomal calcium signalling. (19th September 2012) - Gómez-Suaga, Patricia; Churchill, Grant C.; Patel, Sandip; Hilfiker, Sabine
Abstract : Mutations in LRRK2 (leucine-rich repeat kinase 2) represent a significant component of both sporadic and familial PD (Parkinson's disease). Pathogenic mutations cluster in the enzymatic domains of LRRK2, and kinase activity seems to correlate with cytotoxicity, suggesting the possibility of kinase-based therapeutic strategies for LRRK2-associated PD. Apart from cytotoxicity, changes in autophagy have consistently been observed upon overexpression of mutant, or knockdown of endogenous, LRRK2. However, delineating the precise mechanism(s) by which LRRK2 regulates autophagy has been difficult. Recent data suggest a mechanism involving late steps in autophagic–lysosomal clearance in a manner dependent on NAADP (nicotinic acid–adenine dinucleotide phosphate)-sensitive lysosomal Ca 2+ channels. In the present paper, we review our current knowledge of the link between LRRK2 and autophagic–lysosomal clearance, including regulation of Ca 2+ -dependent events involving NAADP.